Reavaliação dos níveis de tolerância ao desfolhamento, em soja - Carvalho, Nathália Leal de (2015)
The defoliating pests, especially caterpillars, reduce grain yield and cause losses to soybean culture. The levels of action to control these pests were developed more than thirty years ago for cultivars which were different from the current ones regarding the production potential, size, cycle and type of growing, therefore, they may be outdated. In order to evaluate the response to defoliation of soybean cultivars representing a part of the current types in cultivation, experiments were conducted in the experimental area of FAMV/UPF during the harvest 2012/13 in the system of direct seeding. The evaluated cultivars were: BMX Ativa RR (maturity group 5.6 and particular type of growth), BMX Apolo RR (maturity group 5.8 and indeterminate type of growth) and BMX Potência RR (maturity group 6.7 and indeterminate type of growth). Artificial defoliation was performed in phases V9 and R5.1, in levels 0, 8, 17, 33, 50 and 67%. The design was randomized block, factorial, with four repetitions. We evaluated the grain yield and its primary components (number of pods per plant, thousand grain weight and number of seeds per pod), growth indicators and development of plants (height insertions of the first pod, plant height and dry mass). The data were submitted to analysis of variance and means were compared by Tukey test (p ≤ 0,5). For grain yield, we made the correlation analysis with the other variables and the adjustment of its variation due to defoliation (dose-response model for the Weibull distribution). The soybean cultivars BMX Ativa RR and BMX Apolo RR do not tolerate 17% of defoliation in V9 and R5.1; in both cases there is no difference between these stages of development concerning the response to defoliation; the BMX Power RR cultivar does not tolerate 33% of defoliation in V9 and 17% in R5.1